Dengue epidemic in Malaysia: urban versus rural comparison of dengue immunoglobulin G seroprevalence among Malaysian adults aged 35–74 years. (31st July 2020) - Azami, Nor Azila Muhammad; Moi, Meng Ling; Salleh, Sharifah Azura; Neoh, Hui-min; Kamaruddin, Mohd Arman; Jalal, Nazihah Abdul; Ismail, Norliza; Takasaki, Tomohiko; Kurane, Ichiro; Jamal, Rahman
Abstract: Background: A periodic serosurvey of dengue seroprevalence is vital to determine the prevalence of dengue in countries where this disease is endemic. This study aimed to determine the prevalence of dengue immunoglobulin G (IgG) seropositivity among healthy Malaysian adults living in urban and rural areas. Methods: A total of 2598 serum samples (1417 urban samples, 1181 rural samples) were randomly collected from adults ages 35–74 y. The presence of the dengue IgG antibody and neutralising antibodies to dengue virus (DENV) 1–4 was determined using enzyme-linked immunosorbent assay and the plaque reduction neutralisation test assay, respectively. Results: The prevalence of dengue IgG seropositivity was 85.39% in urban areas and 83.48% in rural areas. The seropositivity increased with every 10-y increase in age. Ethnicity was associated with dengue seropositivity in urban areas but not in rural areas. The factors associated with dengue seropositivity were sex and working outdoors. In dengue IgG-positive serum samples, 98.39% of the samples had neutralising antibodies against DENV3, but only 70.97% of them had neutralising antibodies against DENV4. Conclusion: The high seroprevalence of dengue found in urban and rural areas suggests that both urban and rural communities are vital for establishing and sustaining DENV transmission in Malaysia.